Fungal microbiota of sugarcane straw and their ability to produce hydrolytic enzymes - Mendoza-Infante, Nadia G.; Debernardi de la Vequia, Héctor; Hidalgo-Contreras, Juan V.; Múgica-Álvarez, Violeta; Hernández-Martínez, Ricardo (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The microbiota presents in sugarcane (Saccharum officinarum L.) straw can have benefits to produce sustainable crops, also can be used for the development of alternative processes to produce molecules of industrial interest and valorization of biomass and residues unexploited. Therefore, the objective of the present work was the isolation of the fungal microbiota present in the sugarcane straw (CP 72-2082) and its capacity to produce hydrolytic enzymes. The fungal microbiota was isolated by sampling for four months one sampling for month the straw in fields of the "El Potrero" sugar mill in the Veracruz state, Mexico, and soil was also sampled to determine the effect of straw chili on the organic matter content. Furthermore, the capacity of the strains to produce xylanases and cellulases was determined in a Petri dish using birch xylan and carboxymethylcellulose as substrates. Thirty-four strains were isolated from the samples, in all was identified the genera Trichoderma, Fusarium in three and Aspergillus and Penicillum in two. The results indicate that if sugarcane straw is reincorporated into soils where sugarcane is grown, it can have a beneficial impact, 22 isolated strains showed the ability to produce hydrolytic enzymes. The organic matter content in the soils with both shredded and unshredded crop residues showed that chili does not present a benefit to the soil but can contribute beneficial fungal microbiota for various purposes.